From Algorithm Wiki
Step 1: Show that the statement holds for the basis case $ n = 1 $
- $ E(n) = n - 1 $
- $ E(1) = 1 - 1 = 0 $. A tree with one node has zero edges
Step 2: Assume that that summation is true up to n.
Step 3: Show that on the assumption that the summation is true for n, it follows that it is true for n + 1.
- $ E\left(n + 1\right) = n + 1 - 1 $
- $ \Leftrightarrow E(n) + 1 = n $ When adding one node to a tree one edge is added as well
- $ \Leftrightarrow n -1 + 1 = n $
- $ \Leftrightarrow n = n $